Costumbres y tradiciones autóctonas y el turismo cultural del cantón Baba - López Yépez., Marvin Javier (2021)
This investigation of the indigenous customs and traditions, and the cultural tourism of the Baba Canton aims to identify the customs and traditions that are carried out in this town. In addition to how they contribute history, customs and traditions in the development of the tourist industry, since the age of this Canton highlights the historical value it has. This case study seeks to benefit the Decentralized Autonomous Government of the Canton, and the population in general, since what is sought is to promote and preserve customs and traditions, through the tourism industry. It is worth mentioning that several research methods were used such as: quantitative, synthetic, inductive, important types of research were also applied for the development of this case study, in addition, a survey was applied to the population of Canton Baba.